2017
DOI: 10.1056/nejmoa1700827
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation in Extremely Preterm Infants and Respiratory Function at 8 Years

Abstract: Despite substantial increases in the use of less invasive ventilation after birth, there was no significant decline in oxygen dependence at 36 weeks and no significant improvement in lung function in childhood over time. (Funded by the National Health and Medical Research Council of Australia and the Victorian Government's Operational Infrastructure Support Program.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(131 citation statements)
references
References 17 publications
6
124
0
1
Order By: Relevance
“…In a large cohort following preterm infants born between 1992 and 2005 with the mean GA of 25 weeks, Doyle et al [27, 28] showed that despite substantial increases in the use of less invasive ventilation after birth, there was no significant decline in oxygen dependence at 36 weeks and no significant improvement in lung function in childhood at 8 years of age. However, nHFT has increasingly been used in their region since then, and the association of such a change with long-term lung function remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In a large cohort following preterm infants born between 1992 and 2005 with the mean GA of 25 weeks, Doyle et al [27, 28] showed that despite substantial increases in the use of less invasive ventilation after birth, there was no significant decline in oxygen dependence at 36 weeks and no significant improvement in lung function in childhood at 8 years of age. However, nHFT has increasingly been used in their region since then, and the association of such a change with long-term lung function remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,11,15,16 Further supporting the notion of establishing an evidence-based approach is a paper published by Doyle et al; this group followed up preterm infants at 8 years, examining three different cohorts at different time periods. 17 The first cohort was 1991-1992, second 1997 and the third 2005. The authors concluded that despite advances in ventilation and treatment modes, there had been no significant decrease in the number of babies with CNLD.…”
Section: Key Pointsmentioning
confidence: 99%
“…Despite advances in neonatal intensive care, bronchopulmonary dysplasia (BPD) continues to be a common complication in premature infants, especially those born extremely premature (<28 weeks' gestation) . BPD has significant impact on the health of the infant in the neonatal period and early childhood and leads to increased risk of long‐term respiratory issues, such as reactive airway disease, impaired lung function, and exercise intolerance . Severe BPD is also associated with developmental delay and other neuromorbidities in children …”
Section: Introductionmentioning
confidence: 99%
“…1,2 BPD has significant impact on the health of the infant in the neonatal period and early childhood and leads to increased risk of long-term respiratory issues, such as reactive airway disease, impaired lung function, and exercise intolerance. 3,4 Severe BPD is also associated with developmental delay and other neuromorbidities in children. 5 At a pathophysiological level, BPD is characterized by vascular maldevelopment, impaired alveolarization, and lung inflammation.…”
Section: Introductionmentioning
confidence: 99%